Economic Valuation of Mangroves in Sekotong Tengah, West Lombok - Lalu Rizal Rabbany; Mansur Afifi; Diswandi Diswandi; Evi Gravitiani; Mugi Rahardjo (Green Publisher Indonesia, 2025)
This study aims to calculate the economic value of mangrove ecosystems and estimate the average Willingness to Pay (WTP) of the community in Sekotong Tengah Village. Data were collected through observations and interviews with the Contingent Valuation Method (CVM) using the Double-Bounded Dichotomous Choice (DBDC) approach to 100 household respondents. The results showed that the Direct Economic Value (DEV) of mangrove utilization reached IDR 2,790,890,400 per year, while the Indirect Use Value (IUV) derived from ecosystem services was worth IDR 2,845,291,680 per year. The Option Value (OV) is estimated at IDR 2,797,560 per year so that the Total Economic Value (TEV) reaches IDR 6,727,204,152 per year. The estimated average WTP with binary logistic and bivariate probit models were IDR 417,264 (25.17 USD) and IDR 403,452 (24.33 USD) per household per year, respectively. Employment and supply factors negatively affect WTP, while education and income have a positive and significant effect. These results provide insights for mangrove conservation policy and alternative funding for ecosystem protection.